Localization techniques in quantum field theories. (13th October 2017) - Pestun, Vasily; Zabzine, Maxim; Benini, Francesco; Dimofte, Tudor; Dumitrescu, Thomas T; Hosomichi, Kazuo; Kim, Seok; Lee, Kimyeong; Le Floch, Bruno; Mariño, Marcos; Minahan, Joseph A; Morrison, David R; et al.
Abstract: This is the foreword to the special issue on localization techniques in quantum field theory. The summary of individual chapters is given and their interrelation is discussed.